2020
DOI: 10.1039/d0nr05386d
|View full text |Cite|
|
Sign up to set email alerts
|

Ce6-Conjugated and polydopamine-coated gold nanostars with enhanced photoacoustic imaging and photothermal/photodynamic therapy to inhibit lung metastasis of breast cancer

Abstract: Metastasis is the main cause of treatment failure in breast cancer, and integrated phototheranostics is a promising strategy to achieve both precision theranostics and metastasis inhibition. In this work, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…Moreover, combined PTT/PDT treatment was effective in the inhibition of lung metastasis, contrarily to PDT or PTT alone, where some lung metastasis was observed. Moreover, photoacoustic signals of tumours were observed after injection with Ce 6 -PDA@AuNSs, which emphasises its potential simultaneous application as a phototheranostic agent [86]. In another study, Zeng and co-workers [86] reported a Ce6-conjugated and polydopamine (PDA)-coated gold nanostars (AuNSs) for PTT/PDT and photoacoustic imaging.…”
Section: Targeted Therapy In Triple-negative Breast Cancermentioning
confidence: 95%
See 3 more Smart Citations
“…Moreover, combined PTT/PDT treatment was effective in the inhibition of lung metastasis, contrarily to PDT or PTT alone, where some lung metastasis was observed. Moreover, photoacoustic signals of tumours were observed after injection with Ce 6 -PDA@AuNSs, which emphasises its potential simultaneous application as a phototheranostic agent [86]. In another study, Zeng and co-workers [86] reported a Ce6-conjugated and polydopamine (PDA)-coated gold nanostars (AuNSs) for PTT/PDT and photoacoustic imaging.…”
Section: Targeted Therapy In Triple-negative Breast Cancermentioning
confidence: 95%
“…Moreover, photoacoustic signals of tumours were observed after injection with Ce 6 -PDA@AuNSs, which emphasises its potential simultaneous application as a phototheranostic agent [86]. In another study, Zeng and co-workers [86] reported a Ce6-conjugated and polydopamine (PDA)-coated gold nanostars (AuNSs) for PTT/PDT and photoacoustic imaging. The preparation of this material involved the deposit of PDA on the surface of AuNSs by dopamine self-polymerization, resulting in PDA@AuNSs.…”
Section: Targeted Therapy In Triple-negative Breast Cancermentioning
confidence: 95%
See 2 more Smart Citations
“…As one of the essentials in SDT, sonosensitizers have been explored in various tumor therapies [14]. Chlorine e6 (Ce6) was originally employed as a common photosensitizer, but its desirable therapeutic capability and excellent affinition to tumor tissue have made it capable of applying as a sonosensitizer as well [15]. Played as a second generation of chlorine family, Ce6 has aroused an extensive attention in tumor treatment for its desirable ROS generation [16].…”
Section: Introductionmentioning
confidence: 99%